Cultivation of Tawadhu (Humility) and Discipline Among Students at Madin - Rahmania, Nurani; Mun'im, Ali; Kh, Humaidi; Mashuri, Imam; Suryantoro, Dwi Dasa (STAI Miftahul Ula Nganjuk, 2024)
Character building of students can be achieved by habituating good behaviors in daily life. Habituation is a process of forming consistent attitudes and behaviors through repetitive learning, both individually and collectively. In the context of teaching methods in Islamic education, it can be said that